Analisis Sentimen Produk Berdasarkan Review Pelanggan Shopee Menggunakan KNN - Fira Irwannia; Andre Hasudungan Lubis (INCODING: Journal of Informatics and Computer Science Engineering, 2025)
This study aims to conduct sentiment analysis on customer reviews of mukena products available on the Shopee application using the K-Nearest Neighbors (KNN) algorithm. The data used is primary data consisting of 200 reviews collected manually. The analysis process begins with data preprocessing such as case folding, tokenization, stopword removal, and stemming, followed by feature extraction using the TF-IDF method, and classification using the KNN algorithm. The model's performance is evaluated using a confusion matrix. The results show that the proportion of training data and the n_neighbors parameter significantly affect the model's accuracy. A 90% training and 10% testing proportion produced the highest accuracy of 90%. However, with n_neighbors = 3, the best performance was achieved with a 70:30 data split, reaching 81.67% accuracy. This study demonstrates that KNN is an effective method for sentiment analysis on product reviews.